Enhancing PAPR reduction for FBMC-OQAM systems by joint both tone reservation and companding methods - Salima Senhadji; Yassine Mohammed Bendimerad; Fathi Tarik Bendimerad (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
One of the major problems that faces any wireless communication system that apply multicarrier modulation technology is large Peak-to-Average Power Ratio (PAPR). There are divers PAPR reduction methods to solve this problem. Tone Reservation (TR) scheme is one of the most famous PAPR reduction techniques in which a peak cancelling signal is added to the original one in such a way that PAPR will reduce. Companding is another easy PAPR reduction technique in which compression of large amplitude samples and expansion of low one. In this paper, we suggest a new PAPR reduction scheme based on combining tone reservation and companding techniques for FBMC-OQAM systems. The simulation results show that the new scheme (TR&Compd) presents better result in term of PAPR reduction compared to TR and Companding methods taken separately.